2008
DOI: 10.11646/zootaxa.1927.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Comparative larval morphology of eight species of Hypsiboas Wagler (Amphibia, Anura, Hylidae) from Argentina and Uruguay, with a review of the larvae of this genus

Abstract: We studied the external and oral cavity morphology of the tadpoles of eight species of Hypsiboas in the H. albopunctatus, H. faber, H. punctatus and H. pulchellus species groups. After a review of the available information about larval external and oral cavity morphology, no character state seems to be synapomorphic for Hypsiboas. The presence of a fleshy projection in the inner margin of the nostrils and rounded vacuities of the anteromedial surface of the choanae (pending the confirmation of the latter in Hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 0 publications
3
43
0
4
Order By: Relevance
“…In early stages, the spots are located on the neuromast lines, but as the tadpole grows, the spots gradually move apart from the line pattern and increase in size. Kolenc et al (2008) described spots in species of various groups of Hypsiboas and Aplastodiscus and confirmed by SEM study that these are cumuli of neuromasts. The spots reported by Kolenc et al (2008) are similar to the ones observed in Hyloscirtus and probably correspond to the same structure.…”
Section: Groupmentioning
confidence: 53%
See 3 more Smart Citations
“…In early stages, the spots are located on the neuromast lines, but as the tadpole grows, the spots gradually move apart from the line pattern and increase in size. Kolenc et al (2008) described spots in species of various groups of Hypsiboas and Aplastodiscus and confirmed by SEM study that these are cumuli of neuromasts. The spots reported by Kolenc et al (2008) are similar to the ones observed in Hyloscirtus and probably correspond to the same structure.…”
Section: Groupmentioning
confidence: 53%
“…Marinelli et al (1985) and Marinelli and Vagnetti (1988) offer detailed descriptions of development of larval oral features, and detected that in the studied taxa the distal tooth rows hold small, newly formed teeth while the proximal rows are older, formed by thick replacement teeth that push out the smaller ones worn by use. Teeth on the distal rows in the oral disc of Hyloscirtus are smaller than the teeth on the proximal rows (Duellman and Altig, 1978;Ruiz-C. and Lynch, 1982;La Marca, 1985;Cadle and Altig, 1991;Mijares-Urrutia, 1992;Lötters et al, 2005;Kolenc et al, 2008;pers. obs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several other similar examples abound in the literature (Pombal-Jr. and Haddad, 1999;Abrunhosa et al, 2005;Canedo and Pombal-Jr., 2007;Glaw et al, 2010). Likewise, tadpole morphology has been crucial to recognize genera (Cruz, 1982) and diagnose species of several Neotropical anuran groups (Kolenc et al, 2008;Weber and Caramaschi, 2008). Despite the obvious importance of such characters, advertisement calls and larvae morphology of most Brazilian anuran species are unknown (Bastos et al, 2011;Provete et al, 2011), and such data paucity limits comprehensive comparisons needed to resolve problems with amphibian anuran taxonomy.…”
Section: Introductionmentioning
confidence: 99%